Breastfeeding Knowledge, Altitude and Practices of Lactating Mothers in Mwanakia-A Case of Nairobi Metropolis (International Journal of Scientific Research and Management (IJSRM), 2019)
The objective of the study to examine the breastfeeding knowledge, altitude and practices of lactating mothers 0-6 postpartum. This cross sectional study was conducted on 260 lactating women living in Mwanamukia, Nairobi Kenya. A structured questionnaire was used on social, socio-economic characteristics. SPSS version 20 and analyzed using descriptive statistics and Pearson correlation coefficient determined associations. More than half of the respondents were literate, married and lived in male headed households. Others business people, single and Meru ethnicity. Majority 36-40 years age category. Majority (61.6%) participated in urban agriculture. 57.3% of the respondents owned land. 88.5% had heard about exclusive breastfeeding, 96.2% breastfed exclusively for 4 months, 57.7 knew infant should be breastfed immediately after birth, 26.5% breastfeed after2-24 hours of delivery.67.3% frequent suckling does not increase milk production. 46.9% agreed an infant first food breastmilk, 26.5% cow’s milk and 23.8% porridge. 94.2% altitude exclusively breastfeed 6 months, 46.1% believed feed infant breast milk while 30.4% cow’s milk, 23.4% porridge. 48.1% breast milk sufficient, 82.7% colostrum be fed to infant, 17.3% colostrum.81.2% felt good giving infant something to eat before 6 months, 18.8% afraid child well cry. 52.7% felt exclusively breastfed not healthier than exclusively breastfed.94.1% breastfed last child. 50% breastfed immediately, 29.2% gave something after one month, 48.1% gave something after 2 months. 52.3% breastfed on demand, 34.2% when child cried. Illiterate Mothers had inappropriate feeding practices (OR1.578, CI 1.762-2.292). The study concludes that knowledge and practice did not have any relationship, altitude influenced feeding habits.